THE IMPACT OF USING WEBQUEST ON EFL STUDENTS READING COMPREHENSION AT FKIP UNISMUH MAKASSAR - Maya Soraya; Saiful (English Language Teaching Methodology, 2021)
The objective of this study is to assess out the impact of use of WebQuesrt in teaching reading comprehension, which consists of improving students’ understanding of literal reading comprehension in terms of the main idea and supporting details. This study used pre-experimental. In collecting data, the researcher took the drata from pre-test and post-test. The population of the research was the third semester at FKIP Unismuh Makassar that consisted of 20 students. The results of the research showed that te students’ mean score of rthe pre-test before treatment was 52.30%. While after treatment, the mean score of post-test was 94.90%. The result of the data analysis indicated that there was a significant improvement in the students’ reading ability after being taught using WebQuest. It was proved by the result of the statistical analysis of the degree significance p=0.05 with degree of freedom (df)=19 indicated that the t-test (3.6) and t-table is (2.093) and significant. (2-tailed) 0.000. This suggests that the data of post-test as the final result gave the significant improvement. It’s concludedthat the use of WebQuest is able to give greater contribution in teaching and learning reading comprehension.